The Role of Iraqi Universities in Achieving Sustainable Development – Challenges and Solutions (University of Babylon as a Model) - Al-Yassiri, Dr. Amira Saeed Zabala Abdul Hussein Al-Yassiri (Sulaimani Journal for Humanities, 2026)
The important role of the university in determining outputs that align with the nature of this era may sometimes cause it to hesitate in fulfilling its crucial role in driving development. The university is entrusted with providing what society and the labor market need. Additionally, the university’s role is linked to the importance of scientific research in supporting sustainable development, as universities represent the main centers for scientific and applied research, without which it is difficult to achieve any real progress in knowledge, economy, or society. The University of Babylon is one of the universities considered a scientific edifice tasked with multiple responsibilities in Iraqi society, including preparing human resources, conducting scientific research, and contributing to the process of socialization and cultural transmission that ensures shaping students’ awareness and formation, all in service of society and the labor market. Hence, this research aims to identify and diagnose a number of obstacles facing the university and to propose possible solutions to problems that directly affect the university’s performance. The study consists of three chapters: 1. The first chapter clarifies the concept of sustainable development, discusses the university’s importance in sustainable development, and addresses the nature of the obstacles hindering its tasks in society. 2. The second chapter focuses on the importance of scientific research in the university to support sustainable development. 3. The third chapter includes personal interviews with heads of academic departments and directors of technical training centers, scientific research, and laboratories within the University of Babylon, to identify a set of obstacles and challenges that hinder development efforts. The study concludes with several findings through which the researcher proposes relative solutions to the challenges facing universities in achieving sustainable development.
Keywords: Sustainable development; scientific research; university; higher education